Analisis Kualitas Pelayanan Perizinan Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Medan - Ilham Wahyudi; Muhammad Muhammad (LPPM IAI Nasional Laa Roiba Bogor, 2022)
This study aims to describe and analyze the Quality of Licensing Services at the Medan City Investment and One-Stop Integrated Service Office. In this study to collect data the author uses library research methods (Library Research). This technique aims to strengthen the facts in comparing the differences or similarities between theory and practice that the author is researching regarding the problem of “Analysis of the Quality of Licensing Services at the Medan City Investment and One Stop Integrated Service Office”. The results showed that the quality of licensing services at the Medan City DPMPTSP was not maximized and needed improvement, seen from the efforts to improve the quality of services regarding ease of access that were still not maximized due to lack of socialization to the community, and the punctuality of completing the permit letter. Suggestions from this research are to further improve the quality of licensing services regarding completion time in terms of completing permits on time and evaluating the performance of all employees in providing licensing services to the public. Keywords: Quality, Service, Licensing